Tacrine - Benzothiazoles: Novel class of potential multitarget anti-Alzheimeŕs drugs dealing with cholinergic, amyloid and mitochondrial systems - Nepovimova, Eugenie; Svobodova, Lucie; Dolezal, Rafael; Hepnarova, Vendula; Junova, Lucie; Jun, Daniel; Korabecny, Jan; Kucera, Tomas; Gazova, Zuzana; Motykova, Katarina; Kubackova, Jana; Bednarikova, Zuzana; et al. (Bioorganic chemistry, 2021)
A series of tacrine - benzothiazole hybrids incorporate inhibitors of acetylcholinesterase (AChE), amyloid β (Aβ) aggregation and mitochondrial enzyme ABAD, whose interaction with Aβ leads to mitochondrial dysfunction, into a single molecule. In vitro, several of 25 final compounds exerted excellent anti-AChE properties and interesting capabilities to block Aβ aggregation. The best derivative of the series could be considered 10w that was found to be highly potent and selective towards AChE with the IC50 value in nanomolar range. Moreover, the same drug candidate exerted absolutely the best results of the series against ABAD, decreasing its activity by 23% at 100 µM concentration. Regarding the cytotoxicity profile of highlighted compound, it roughly matched that of its parent compound - 6-chlorotacrine. Finally, 10w was forwarded for in vivo scopolamine-induced amnesia experiment consisting of Morris Water Maze test, where it demonstrated mild procognitive effect. Taking into account all in vitro and in vivo data, highlighted derivative 10w could be considered as the lead structure worthy of further investigation.
Keywords: proteinové agregáty; Protein Aggregates; Dose-Response Relationship, Drug; vztah mezi dávkou a účinkem léčiva; Acetylcholinesterase; neuroprotektivní látky; mitochondrie; acetylcholinesterasa; Acetylcholinesterase Inhibitors; Neuroprotective Agents; Alzheimer’s disease; cholinergní látky; takrin; Amyloid β; Tacrine; Alzheimer Disease; ABAD; Cholinergic Agents; Benzothiazoles; amyloidní beta-protein; Benzothiazole; 3-Hydroxyacyl CoA Dehydrogenases; vztahy mezi strukturou a aktivitou; Humans; Molecular Structure; molekulární struktura; Mitochondria; Alzheimerova nemoc; Amyloid beta-Peptides; Structure-Activity Relationship; MTDLs; 3-hydroxyacyl-CoA-dehydrogenasy; Enzyme Inhibitors; lidé; benzothiazoly; inhibitory enzymů